Adoption of Fintech Apps for Insurance Purchases: A Study on Consumer Behavior in Mumbai Suburban (Journal of Informatics Education and Research, 2026)
The adoption of financial technology (fintech) applications for insurance purchases is reshaping the insurance sector by enhancing accessibility, transparency, and user convenience. However, in suburban Mumbai, adoption rates remain relatively low due to barriers such as digital literacy gaps, trust concerns, and socio-economic disparities. This study investigates the key factors influencing consumer behavior in fintech adoption for insurance purchases, with a particular focus on trust, ease of use, and digital literacy.A structured survey was conducted among 206 respondents in suburban Mumbai, utilizing a stratified random sampling technique to capture diverse socio-economic backgrounds. The study employs statistical methods such as multiple regression analysis and Structural Equation Modeling (SEM) to assess the impact of psychological and socio-economic determinants on fintech adoption.Key findings indicate that ease of use is the most significant predictor of fintech adoption, aligning with the Technology Acceptance Model (TAM). While trust and digital literacy were not found to have a direct impact on adoption, they significantly influence consumer confidence, which in turn affects adoption rates. The study also highlights that higher education levels correlate positively with fintech adoption, while gender differences in adoption behavior are narrowing.The findings suggest that fintech firms should prioritize user-friendly design, financial literacy initiatives, and trust-building mechanisms to drive greater adoption of digital insurance platforms. Policymakers should promote targeted digital awareness campaigns to bridge the digital literacy gap and enhance financial inclusion.This study contributes to the growing literature on fintech adoption in emerging markets and provides valuable insights for fintech developers, insurers, and regulators aiming to improve consumer engagement. Future research should explore additional socio-economic variables and behavioral aspects influencing fintech adoption trends in other suburban and rural settings.